Jet suppression and jet substructure in Pb plus Pb and Xe plus Xe collisions with the ATLAS detector - Onofre, A. (2019)
This short summary presents latest measurements of the nuclear modification factor, RAA, for R = 0.4 jets in Pb+Pb collisions at with the ATLAS detector at the LHC. The analysis is performed over a large range of transverse momentum, up to pT = 1 TeV, and differentially in jet pT, rapidity, and collision centrality. The jet RAA is measured also differentially in the jet mass, m, which provides new information on the dependence of the energy loss on the substructure of jets. Latest results by ATLAS on the dijet momentum balance in Xe+Xe collisions at are presented and compared to the same quantity measured in Pb+Pb collisions at . These recent measurements should help us understand mechanisms of parton energy loss and properties of hot and dense matter created in heavy-ion collisions.